Current Status of CTCs as Liquid Biopsy in Lung Cancer and Future Directions - Zhang, Zhuo; Ramnath, Nithya; Nagrath, Sunitha (Frontiers in Oncology, 2015)
Circulating tumor cells (CTCs) have garnered a lot of attention in the past few decades. Isolation of these rare cells form the billions of blood cells has been a challenge until recent times. With the advent of new sensitive technologies that permit live cell isolation and downstream genomic analysis, the existing paradigm of CTC research has evolved to explore clinical utility of these cells. CTCs have been identified as prognostic and pharmacodynamic biomarkers in many solid tumors, including lung cancer. As a means of liquid biopsy, CTCs could play a major role in the development of personalized medicine and targeted therapies. This review discusses the state of various isolation strategies, cell separation techniques and key studies that illustrate the application of liquid biopsy to lung cancer.